MILK CURD CUTTING TIME DETERMINATION IN CHEESEMAKING - I, T. Smykov (Пищевые системы)
The article presents the results of manufacture and experimental studies of the use of hot wire method, implemented on standard elements of automation equipment, for online determination of milk curd readiness to cutting in the cheesemaking process. the values of the elastic modulus for different types of cheeses at the moment of milk curd readiness to cutting are determined. the statistical processing of the results of experimental studies was carried out. It is shown that the average value of the elastic modulus at this moment is 1.68 c.u., and the standard deviation is 0.017 c.u. The investigations have been performed to evaluate the effect of the type of enzyme preparation on the milk curd properties and the accuracy of determining the moment of milk curd readiness to cutting, obtained with their use. It is established that the value of the elastic modulus, specific for the moment of milk curd readiness to cutting, will be different for each type of enzyme preparation. The average value of the elastic modulus of the curd at the moment of its readiness to cutting with the use of different types of enzyme preparations can vary from 1.5 to 1.95 c.u., but it is a constant value for each of them. The researches showed that the hot wire method could be used for mechanization and automatization of the industrial manufacture process